Developing Augmented Reality-Based Interactive Learning Media to Enhance Students’ Mathematical Communication Skills and Self-Confidence - yanuarto, Wanda Nugroho; Arifudin, Imam (Desimal: Jurnal Matematika, 2026)
The growing integration of digital technology in education has increased the demand for innovative mathematics learning environments that support both cognitive and affective student development. However, mathematics instruction in many secondary schools remains teacher-centered and procedural, limiting students’ opportunities to communicate mathematical ideas and develop confidence during learning activities. Although Augmented Reality (AR) has shown strong potential in mathematics education, previous studies have primarily focused on conceptual understanding and achievement, while the simultaneous development of mathematical communication skills and self-confidence remains underexplored. This study aimed to develop AR-based interactive learning media for Systems of Linear Equations in Two Variables and examine its validity, practicality, and effectiveness in improving students’ mathematical communication skills and self-confidence. The study employed a Research and Development approach using the ADDIE model involving 44 eighth-grade students at SMP Muhammadiyah 2 Purwokerto, Indonesia. Data were collected through mathematical communication tests, self-confidence questionnaires, interviews, observations, validation sheets, and student response questionnaires. The findings revealed that the developed media achieved high validity and practicality levels, while the experimental group demonstrated significantly higher learning improvement than the control group (p < .05). The large effect size indicates that immersive AR-supported learning facilitated stronger conceptual understanding, mathematical communication, and student confidence. The study concludes that AR-based learning media can function as an effective pedagogical environment for more participatory and meaningful mathematics learning.